Annually Laminated Lake Sediments - Tylmann, Wojciech (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The collection of papers presented in this book illustrates the recent progress made in varved sediment research and highlights the large variety of methodological approaches and research directions applied. The contributions cover monitoring of modern sediment fluxes using sediment traps; geochronological and sedimentological analyses of annually laminated lacustrine sediments or varves; and multiproxy investigations, including geochemical and biological proxies as well as spatiotemporal analyses based on multicore studies supported by satellite images and X-ray computed tomography (CT). The scientific issues discuss the influences of hydrological and climatological phenomena on short-term changes in sediment flux, the relationships between biogeochemical (limnological) processes in the water column and the formation of varves, the preservation of environmental signals in varved sediments, and possibilities of synchronizing varved records with other high-resolution environmental archives such as tree rings.